Wpływ wysiłku fizycznego wybranych dyscyplin sportowych na habitualną postawę ciała = The effect of physical exercise on selected sports on habitual posture - Mrozkowiak, M.; Sokołowski, M.; Kaiser, A. (Journal of Education, Health and Sport, 2016)
Mrozkowiak M., Sokołowski M., Kaiser A. Wpływ wysiłku fizycznego wybranych dyscyplin sportowych na habitualną postawę ciała = The effect of physical exercise on selected sports on habitual posture. Journal of Education, Health and Sport. 2016;6(10):131-157. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.160499 http://ojs.ukw.edu.pl/index.php/johs/article/view/3930 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 12.10.2016. Wpływ wysiłku fizycznego wybranych dyscyplin sportowych na habitualną postawę ciała The effect of physical exercise on selected sports on habitual posture 1Mrozkowiak M., 2Sokołowski M., 3Kaiser A. 1Bioergonsport, Płock, Polska 2Akademia Wychowania Fizycznego, ul. Królowej Jadwigi 27/39, Poznań, Polska 3Wyższa Szkoła Bankowa w Poznaniu, Polska Słowa kluczowe: postawa habitualna, sport Streszczenie Wstęp. Wpływ ćwiczeń fizycznych na rozwój osobniczy są funkcją jego intensywności i długotrwałości. Celem podjętych badań jest wykazanie wpływu treningu sportowego właściwego danej dyscyplinie sportowej na habitualną postawę ciała sportowca Materiał, przedmiot metoda. Pomiarów 35 przestrzennych cech habitualnej postawy ciała dokonano wśród 151 zawodników judo, zapasów, piłki siatkowej, piłki nożnej i szermierki. metodą fotogrametryczną. Wyniki. Opisano postawę habitualną sportowca właściwą każdej dyscyplinie sportowej, określono istotność różnic z przyjętymi wielkościami cech postawy habitualnej osobników nie uprawiających sportu klasyfikowanego. Wnioski. (1) Stan zdrowia uprawiających sport kwalifikowany może zależeć od wiedzy, umiejętności i wrażliwości prowadzącego szkolenie sportowe. Istotnym kryterium oceny stosowanych obciążeń w sportach asymetrycznych może być diagnostyka postawy ciała, umożliwiająca korektę metod treningowych i stosowanych środków w jej ramach. Wskazane jest wprowadzenie wszechstronnego szkolenia zawodników i doskonalenia funkcjonalnej równowagi poszczególnych grup mięśniowych, szczególnie w dyscyplinach asymetrycznych, (2) Należy wprowadzić właściwą selekcje w naborze młodych adeptów klubów sportowych w oparciu o systematyczne badania lekarskie, (3) Zaburzenia statyki postawy ciała w wieku dojrzałego zawodnika mogą być konsekwencją nie stosowania zasad treningu holistycznego i błędów w początkowym etapie szkolenia, błędów w rozgrzewce i braku ćwiczeń kształtujących nawyk postawy prawidłowej w jej ramach, (4) Zrealizowane badania nie dają pełnego obrazu zmian w postawie ciała po wpływem pracy charakterystycznej dla danej dyscypliny sportowej. Keywords: habitual posture, sport Summary Admission. The impact of physical exercise on the development of the individual are a function of its intensity and duration. The aim of the study is to demonstrate the influence of sports training appropriate for their sport habitual posture athlete The material object of the method. Measurements 35 spatial characteristics of habitual posture made of 151 players judo, wrestling, volleyball, football and fencing. photogrammetric method. Results. Described the attitude of habitual athlete right every sports discipline, defined the significance of differences of values accepted traits of habitual attitudes of individuals not engaged in sport classified. Conclusions. (1) The health status of athletes qualified may depend on the knowledge, skills and sensitivity leading sports training. An important criterion for evaluating the load in sports may be asymmetric diagnostics of body posture, enabling correction of training methods and means used within it. It is the introduction of comprehensive training of players and improve functional balance of individual muscle groups, especially in the disciplines of asymmetric (2) Enter the correct selections in recruiting young students of sports clubs based on regular medical examinations, (3) disorders static posture in adulthood player may be the consequence of not applying the principles of training holistic and errors in the initial training phase, errors in the warm-up and lack of exercise forming the habit of correct posture within it, (4) Realized studies do not give a complete picture of changes in body posture the influence of labor characteristic of the sport.